Inventarisasi Jenis-Jenis Gulma Berdaun Lebar Pada Lahan Tanaman Jagung Zea Mays L. Di Desa Samangki Kec. Simbang Kab. Maros - Rita Tosang; Elis Tambaru; Andi Masniawati (Jurnal Ilmu Alam dan Lingkungan, 2019)
Inventory broadleaf weeds on corn land Zea mays L. in Samangki village, Simbang subdistrict, Maros district has done on Maret-April 2019. The purpose of this study was to inventory the types of broadleaf weeds on corn land in Samangki Village, Simbang Subsdistrict, Maros District. The research method used Cruise Method. Analysed data with identification and describe the sample which habitus of the plants. Research result showed that species broadleaf weeds were 2 classis: Monocotyledoneae dan Dicotyledoneae. Total number of broadleaf weeds were 33 species and 17 familia. Broadleaf weeds in first location which age corn 3 week were 14 species dan 9 familia, second location which age corn 6 week were 25 species dan 15 familia and three location which age corn 8 week were 26 species dan 16 familia. Asteraceae familia have more species that 6 species, were Ageratum conyzoides L., Emilia sonchifolia (L.) DC ex. Weight, Eupatorium odoratum (L.), Vernonia cinerea L., Tridax procumbens L., dan Eleutheranthera ruderalis (Sw.) Sch.Bip.